Study of adsorption isotherms of some industrial dyes using atbalkite clay (College of Basic Education Research Journal, 2025)
This research dealt with a study of  treatment of some industrial and similar dyes with (o-tolidin (2,6-dimathelanlin) (2,4,6-Tri-mathelanlin) by applying adsorption technique using material  Atablekite clay available in  western regions of Iraq,  characterized with mass availability and  at low economic cost. This material was prepared by crushing, washing, drying and studying it for adsorption of the above – mentioned  dyes.             Aqueous solutions of these dyes were prepared using specific proportion of water with solvent (ethanol) and determining  optimum conditions for the best amount of  adsorbent, which was (0.1g),as well as the best concentration, temperature and pH, using  single – meal method. ln this research, thermodynamic values were calculated. (∆S,∆H,∆G) at equilibrium. It became clear through this research that  enthalpy value was equal to a negative value (,∆H=-) meaning that  reaction is exothermic, and  value of (∆G=-) indicates  spontaneity of reaction. It also became clear for researchers that  adsorption process of these dyes has a physical characteristic, physical adsorption, meaning association of adsorbent and  adsorbed material through van der Waals bonds.           This research also included calculating some dye adsorption isomers such as Langmuir-Freundlich and obtaining some important values such as(b) (QMAX) and (n) which provide confirmation of  values obtained in thermodynamic study.
Keywords: Adsorption; Dyes; Isotherms